Enhancement of DNA detection with magnetofluidics - Lim, Chee Dak (2017)
Microfluidic is a technology which allows fluid to be studied on a micro scale. This technology development has advanced and is widely used for different applications in the medical field. Magnetofluidic is a microfluidic method which involves using magnet and ferrofluid to manipulate fluid. Therefore, this brings us to enhance the detection of DNA using magnetofluidic.